Journal of Exposure Science & Environmental Epidemiology Official journal of the International Society of Exposure Science - Hubal, Elaine A. Cohen; SpringerLink (Online service) (New York : Nature Publishing Group US : Imprint: Springer Nature.)
Journal of Exposure Science and Environmental Epidemiology (JESEE) aims to be the premier and authoritative source of information on advances in exposure science for professionals in a wide range of environmental and public health disciplines. JESEE publishes research presenting significant advances in exposure science and exposure analysis, including development and application of the latest technologies for measuring exposures, and innovative computational approaches for translating novel data streams to characterize and predict exposures. Reported results should further understanding of the relationship between environmental exposure and human health, describe evaluated novel exposure science tools, or demonstrate potential of exposure science to enable decisions and actions that promote and protect human health. JESEE is particularly interested in publishing research that integrates information from exposure science, epidemiology, and toxicology to provide holistic understanding of the most pressing environmental and public health concerns.
Keywords: Medicine; Epidemiology; Medicine/Public Health, general; Epidemiology